Teaching Practice Program in the College of Education – its Strengths and Challenges - Gebretinsae, Dawit Yikealo; Karvinen, Ikali (Open Science Journal, 2018)
This research was conducted to evaluate the teaching practice program practiced every second semester in the College of Education (CoE) found in Eritrea Institute of Technology, Mainefhi. It explored the challenges and strengths of the program. To conduct this qualitative study, a questionnaire and a focused group discussion was used. A total of 104 participants (cooperating teachers, student teachers and supervisors)were selected for the study. The findings reveal that the teaching program in the CoE is practiced in a short time span with difficulties in materializing the proposed budget by the CoE and other challenges that vitiate its quality. However, the involvement of the cooperating teachers (CTs) and supervisors is satisfying. Majority of the student teachers (STs) felt that the practice plays a great role in preparing them for the teaching profession. Therefore, generally solving the budget implementation issue and the minor drawbacks of the program will definitely make it contribute a lot in producing qualified teachers. Finally, these findings are expected to mitigate the limitations of the program and raise the outcome of the practice. Besides, other initial teacher education institutes may benefit from the study findings.